TINJAUAN AGROFORESTRI DAN PENDEKATAN KARAKTER BUDAYA LOKAL DALAM PEMULIHAN LAHAN KRITIS DI KABUPATEN LIMAPULUH KOTA - Desi Widia Kusuma (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2017)
Limapuluh Kota Regency has the largest critical land in West Sumatra. Based on the Decree of the Director General of Management of Watershed and Forestry, Ministry of Forestry Number: SK.4 / V-DAS / 2015 on National Forest Critical Map and Data of 2013, there is a critical land area of 94,593.7 ha and very critical land area of 32,488 ha In Limapuluh Kota Regency. This number will continue to grow if no appropriate recovery is done. With hilly dominated topography and large slopes of 40%, the Agroforestry Program is well suited to be developed to address critical lands in Limapuluh Kota Regency. The effort to restore critical land in Limapuluh Kota Regency must be integrated in between technology and character of local culture. This study aims to obtain information on the recovery of critical land with agroforestry systems and the characteristics of the Minangkabau Community. The method used is qualitative descriptive with interview technique and document tracking. The results of the study indicate that the cultural character of the Minangkabau Community should be a concern / consideration in the development of the Agroforestry Program as the basis for the involvement of community participation in Limapuluh Kota Regency in order to succeed. Some of the characters adopted by the Minangkabau community in decision-making are: authority, deliberation/consensus, leadership, critical attitude toward change, egalitarian and democracy and ulayat lands. The character can be considered in applying agroforestry program in Limapuluh Kota Regency.Keywords: critical land, agroforestry, character of local culture, Minangkabau Society